A systematic mapping review of foreign direct investment by multinational corporations in emerging economies - Ahmed Nazzal; Angels Monserrat Niñerola; Maria-Victoria Sánchez-Rebull; Maria Glòria Barberà-Mariné (Humanities & Social Sciences Communications)
Abstract This study aims to provide new insights into the evolution and current state of the literature on foreign direct investment (FDI) and multinational corporations (MNCs) over the past five decades, with a particular focus on emerging economies. Using a bibliometric methodology, the study analyzes 1386 articles authored by 2335 researchers and published in 461 journals between 1987 and 2023. The results show that the literature on FDI by MNCs in emerging economies can be broken down into subthemes such as FDI impacts on economic development, the internationalization of emerging economy multinationals, the effects of institutional factors on MNC behavior and performance and the need to rethink existing international business theories to explain how emerging economy multinationals have changed over time. Additionally, the citation analysis confirmed the observations derived from literature trends and thematic mapping analyses. The results also reveal a significant increase in publications since 2010. Eighty-five percent of the articles were published in the last ten years, yet those articles received a sufficient number of citations for inclusion in the network (56.8%). This study contributes to the international literature by expanding on previous reviews of the topic and providing intriguing insights and recommendations for future research. The current article provides several starting points for practitioners and researchers investigating FDI. It contributes to broadening the scope of the field and suggesting avenues for future studies.